Biological Role of MYCN in Medulloblastoma: Novel Therapeutic Opportunities and Challenges Ahead - Shrestha, Sumana; Morcavallo, Alaide; Gorrini, Chiara; Chesler, Louis (Frontiers in Oncology, 2021)
The constitutive and dysregulated expression of the transcription factor MYCN has a central role in the pathogenesis of the paediatric brain tumour medulloblastoma, with an increased expression of this oncogene correlating with a worse prognosis. Consequently, the genomic and functional alterations of MYCN represent a major therapeutic target to attenuate tumour growth in medulloblastoma. This review will provide a comprehensive synopsis of the biological role of MYCN and its family components, their interaction with distinct signalling pathways, and the implications of this network in medulloblastoma development. We will then summarise the current toolbox for targeting MYCN, and highlight novel therapeutic avenues that have the potential to results into better-tailored clinical treatments.